Development of quality control system for fingerprint comparison processes - Shiquan Liu; Zhongliang Mi; Francisco Valente Gonçalves; Jian Wu; Kelly Ayers (Wolters Kluwer Medknow Publications, 2017)
Fingerprint evidence played an important role in investigation, prosecution, and trial process due to the belief of its uniqueness and unchanged characteristics. However, in recent years, the science behind the process of fingerprint comparisons has been questioned. Main research questions have been focusing on the opaqueness within the comparison processes, subjective judgments, lack of universal standards, no error rate expression on final conclusions, and poor scientific fundamental research data. Facing the above-mentioned questions, this paper aims to suggest a quality control system (QCS) for fingerprint comparison processes. This QCS is based on the use of software (PiAnoS) and its technological features, being able to provide a data management model to increase the transparency and quality of fingerprint comparison processes.